The oxypropylation of olive stone and the use of the ensuing polyols for the synthesis of novel polyesters and polyurethanes based on renewable resources - Matos, M.C. (2011)
The development of polyols by the oxypropylation of abundant and renewable vegetable and animal resources constitutes an original approach to the exploitation of the biomass. Cellulose, starch, chitosan, chitin, different types of lignins, cork and more complex structures like sugar beet pulp, are among the documented examples. All these systems displayed a similar pattern in terms of the grafting of short poly(propylene oxide) (POP) chains from the OH groups of the substrate, albeit of course each situation required a specific set of optimized experimental conditions to transform the natural solid into a viscous polyol. The transformation of these polyols into polyurethanes is the only operation which has been studied to date as a form of their exploitation into polymer materials. In this work, the more promissing were selected for chemical modifications involving first ester and urethane formations with aliphatic and aromatic monofunctional reagents.